Enhancing Safety in Water Transport System Based on Internet of Things for Developing Countries. (14th February 2016) - Mohaimenuzzaman, Md; Monzurur Rahman, S. M.; Alhussein, Musaed; Muhammad, Ghulam; Abdullah Al Mamun, Khondaker
Abstract : Accidents in inland waterways in developing countries are a regular phenomenon throughout the year causing deaths, injuries, monetary loss, and a significant amount of missing people. In consequence, a lot of families are losing their dear ones leading to much misery. The above context demands an intelligent, safe, and reliable water transport system for the developing countries. The concept of Intelligent Transport System (ITS) can be applied to develop such system; however, there are issues with ITS and Internet of Things (IoT) unlocks a new way of developing it. This paper proposes a model to transform the water transport system into an intelligent system based on IoT. IPv6 based machine-to-machine (M2M) protocol, 3G telecommunication technology, and IEEE 802.15.4 network standard play a significant role in this proposed IoT based system.